From "the Rest" to "the West"? Rights of Indigenous Peoples and the Western Bias in Norm Diffusion Research1. Issue 4 (31st August 2015) - Steinhilper, Elias
Abstract : This article discusses the construction and diffusion of the Rights of Indigenous Peoples (RIP). RIP have only scarcely been addressed in detail from a human rights (HR) norm diffusion perspective, yet it is instructive for gaining further insights into norm dynamics, due to the marginalization of indigenous communities within their countries of origin as well as the concentration of indigenous populations in the Global South. RIP have hence been qualified as a "least likely" case for internationalization. Mainstream diffusion literature has mostly focused on the proliferation of liberal Western norms, radiating from "the West" to "the Rest." Powerful Western states as norm entrepreneurs have been explicitly included into models of normative change (for example, the spiral model). My qualitative process tracing research, however, presents a distinct pattern: Indigenous peoples themselves, in alliance with transnational advocacy networks and sympathetic states (to a considerable extent Latin American), have succeeded in constructing a new HR norm manifested in the UN Declaration on RIP. Among the skeptical norm takers were mainly liberal democracies such as the United States. To understand this puzzle, I combine Acharya's norm localization concept with its focus on "cognitive priors" with the norm appropriation framework recently suggested by Großklaus.